2018
DOI: 10.1371/journal.pone.0205490
|View full text |Cite
|
Sign up to set email alerts
|

High versus low attenuation thresholds to determine the solid component of ground-glass opacity nodules

Abstract: ObjectivesTo evaluate and compare the diagnostic accuracy of high versus low attenuation thresholds for determining the solid component of ground-glass opacity nodules (GGNs) for the differential diagnosis of adenocarcinoma in situ (AIS) from minimally invasive adenocarcinoma (MIA) and invasive adenocarcinoma (IA).MethodsEighty-six pathologically confirmed GGNs < 3 cm observed in 86 patients (27 male, 59 female; mean age, 59.3 ± 11.0 years) between January 2013 and December 2015 were retrospectively included. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…According to phantom study and clinical practice, we determined the consistency between solid component size on thin-section CT evaluated by MPVR and PIS to predict invasive degree of SSNs. On MPVR images, the component within SSN with the CT value of greater than −350 HU was defined as solid component and displayed as red part consistent with the color of pulmonary vessels, which was close to the results of previous studies ( 32 - 35 ). Cohen et al ( 34 ) reported that software measurements of solid component at a threshold of -350 HU showed the highest agreement without significant difference with invasive component sizes on pathology with a mean difference of −0.12 mm (P>0.05).…”
Section: Discussionsupporting
confidence: 87%
“…According to phantom study and clinical practice, we determined the consistency between solid component size on thin-section CT evaluated by MPVR and PIS to predict invasive degree of SSNs. On MPVR images, the component within SSN with the CT value of greater than −350 HU was defined as solid component and displayed as red part consistent with the color of pulmonary vessels, which was close to the results of previous studies ( 32 - 35 ). Cohen et al ( 34 ) reported that software measurements of solid component at a threshold of -350 HU showed the highest agreement without significant difference with invasive component sizes on pathology with a mean difference of −0.12 mm (P>0.05).…”
Section: Discussionsupporting
confidence: 87%
“…Information about the characteristic findings of AIS and MIA is important given that patients have a 100% or near‐100% chance of disease‐free survival, respectively, if these lesions are completely resected 4,5 . Despite the growing number of published cases, no definitive rates for recurrence have so far been reported in patients with AIS 15–22 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several recent studies have reported the characteristics of invasive and noninvasive adenocarcinoma imaging patterns 2–4 . Nonetheless, there is insufficient evidence in the current literature about the differences in the rate of recurrence and prognosis between AIS and MIA 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Cohen et al ( 13 ) suggested that segmentation of the solid component shows the best performance at a threshold of −350 HU, and measurements on mediastinal windows (window width, 400 HU; level, 30 HU) were significantly smaller than the actual sizes of the invasive components. In the same context, Lee et al ( 20 ) compared two different thresholds, namely, −160 HU and −400 HU. They concluded high diagnostic accuracy in −400 HU for determining the presence of solid components of SSNs, whereas low sensitivity and negative predictive value in −160 HU.…”
Section: Discussionmentioning
confidence: 99%